A New Approach for the Approximations of Solutions to a Common Fixed Point Problem in Metric Fixed Point Theory. (27th October 2016) - Altun, Ishak; Al Arifi, Nassir; Jleli, Mohamed; Lashin, Aref; Samet, Bessem
Abstract : We provide sufficient conditions for the existence of a unique common fixed point for a pair of mappings T, S : X → X, where X is a nonempty set endowed with a certain metric. Moreover, a numerical algorithm is presented in order to approximate such solution. Our approach is different to the usual used methods in the literature.